2016
DOI: 10.1093/alcalc/agv128
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Marketing on Twitter and Instagram: Evidence of Directly Advertising to Youth/Adolescents

Abstract: The alcohol industry is in violation of their proposed self-regulation guidelines for digital marketing communications on Instagram. While Twitter's age-gate effectively blocked direct to phone updates, unhindered access to post was possible. Everyday our fictitious profiles, even those as young as 13, were bombarded with alcohol industry messages and promotional material directly to their smartphones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 30 publications
5
49
0
4
Order By: Relevance
“…However, establishing causality between promotional activity and alcohol use is methodologically and ethically problematic, especially where subjects are under the legal age for purchasing alcohol. This is compounded further by the difficulty in separating advertisements aimed at adults from those aimed at children and young people, and the growth of marketing in youth focused outlets, in formats that are likely to appeal to children and young people (Hastings et al ., 2010; Barry et al ., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…However, establishing causality between promotional activity and alcohol use is methodologically and ethically problematic, especially where subjects are under the legal age for purchasing alcohol. This is compounded further by the difficulty in separating advertisements aimed at adults from those aimed at children and young people, and the growth of marketing in youth focused outlets, in formats that are likely to appeal to children and young people (Hastings et al ., 2010; Barry et al ., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…One study was able to access and subscribe to 100% of official alcohol YouTube channels using fictitious underage user profiles [57]. Using similar procedures, 22 official alcohol pages were fully accessible on Instagram and Twitter [14]. These findings call for regulatory changes, such as tightening restrictions on accessibility to official alcohol company pages via social media platforms by implementing age restrictions for YouTube, Instagram and Twitter and by making already existing age restrictions harder to bypass.…”
Section: Traditional and Digital Exposure Venuesmentioning
confidence: 99%
“…Further, codes aimed at restricting underage individuals from viewing digital alcohol advertisements can be easily bypassed [13]. In some cases, age verification restrictions are nonexistent on social media platforms [14]. Specifically, a recent study examining youth access to alcohol brands found that on Instagram, users of any age were able to follow alcohol brand pages and were subsequently exposed to an average of 362 alcohol advertisements within the past 30 days [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the fastest growing media exposures are Internet-based (Barry, Bates, et al, 2015;McClure et al, 2016). This is an important area for research because Internet access is widely available to youth, with 92% of teens reporting daily use (Lenhart, 2015).…”
Section: Introductionmentioning
confidence: 99%